The Effect of The 'Illat Conditions of The Law on The Difference of Opinion of The Majority of Ulama and Ibn Taimiyah in The Law of Buying and Selling Gold in a Non-Cash Manner (Analysis of Fatwa DSN MUI No. 77/DSN-MUI/V/2010 Concerning The Buying and Selling of Gold in Cash) - Mujahidin, Ikhwanul; Khotimah, Umi Khusnul; Hidayat, Hidayat (Program Pascasarjana UMSB, 2024)
There are two opinions of scholars in the law of buying and selling gold for cash, the first is the majority of scholars who stated that it is forbidden to buy and sell gold for cash with the existence of sharîh arguments stating the prohibition and the second is the opinion of Ibn Taimiyyah who stated that the law of buying and selling gold for cash is permissible, with the disappearance of ʻIllat Hukum from gold.The author uses qualitative research methods with an approach that is descriptive analysis by using primary data obtained from the Fatwa DSN-MUI and secondary data obtained through the collection of literature related to this research.The majority of scholars view that it is not possible to change the law of buying gold in cash from haram to mubah with the disappearance of ʻIllat Hukum from gold because it does not fulfil the requirements of ʻIllat Hukum while Ibn Taimiyyah views the change as possibleKeyword: 'Illat Law; Selling Gold; Ulama